Quantifying the effects of photoreactive dissolved organic matter on methylmercury photodemethylation rates in freshwaters. (30th December 2016) - Klapstein, Sara J.; Ziegler, Susan E.; Risk, David A.; O'Driscoll, Nelson J.
Abstract: The present study examined potential effects of seasonal variations in photoreactive dissolved organic matter (DOM) on methylmercury (MeHg) photodemethylation rates in freshwaters. A series of controlled experiments was carried out using natural and photochemically preconditioned DOM in water collected from 1 lake in June, August, and October. Natural DOM concentrations doubled between June and August (10.2–21.2 mg C L −1 ) and then remained stable into October (19.4 mg C L −1 ). Correspondingly, MeHg concentrations peaked in August (0.42 ng L −1 ), along with absorbances at 350 nm and 254 nm. Up to 70% of MeHg was photodemethylated in the short 48‐h irradiation experiments, with June having significantly higher rates than the other sampling months ( p  < 0.001). Photodemethylation rate constants were not affected by photoreactive DOM, nor were they affected by initial MeHg concentrations ( p  > 0.10). However, MeHg photodemethylation efficiencies (quantified in moles MeHg lost/moles photon absorbed) were higher in treatments with less photoreactive DOM. Congruently, MeHg photodemethylation efficiencies also decreased over summer by up to 10 times across treatments in association with increased photoreactive DOM, and were negatively correlated with DOM concentration. These results suggest that an important driver of MeHg photodemethylation is the interplay between MeHg and DOM, with greater potential for photodemethylation in freshwaters with more photobleached DOM and lower DOM content. Environ Toxicol Chem 2017;36:1493–1502. © 2016 SETAC